Factors influencing the purchase intention of cruelty-free cosmetics in portuguese consumers: an exploratory approach - Silva, Ana (2021)
The planet’s sustainability and animal welfare are causes which are increasingly being supported by consumers and embraced by brands. Specifically, in the cosmetic industry, cruelty-free brands offer the consumer the possibility of using products that do not perform tests on animals in their development. This study aimed to identify the dimensions which may be related to the purchase intention of this type of products. It was possible to verify that the use of social media, favorable attitudes towards animal cruelty-free cosmetics, altruism and environmental knowledge are positively related to the purchase intention of these products. It was also discovered that financial sensitivity is not positively related to the purchase intention of cosmetics exempt of animal cruelty. Through multiple logistic regression models, it was also found that higher values in the dimensions “Attitudes towards cruelty-free products” and “Environmental knowledge” represent higher chances of intention to buy these products. The results confirm a series of previous studies and allow the possibility of elaborating suggestions on future strategies to be developed by cruelty-free brands.